THE PUBLIC INVESTMENT NATIONAL SYSTEM. A CRITICAL ANALYSIS - Andía V., Walter (2004)
The present article explains some comments on the components of the Public Investment National System (PINS), with the only purpose of contributing to perfecting its implementation, thus reaching its intended aim.